The Influence of Leadership Style, Position Promotion and Work Stress on Employee Performance PT. Perkebunan Nusantara IV Regional II Adolina Gardens - Simanjuntak, Wahyu Ramadhan; Hutapea, Silvani Oktaris; Ginting, Ella Enjella Br; Hakim, Habib; M. Tahir (International Journal Of Economics Social And Technology (IJEST), 2024)
Quantitative research involving 122 respondents and aims to explain how leadership style, stress at work, and work promotions influence employee performance at PT. Adolina Gardens Perkebunan Nusantara IV Reglonal II. The results of this research show that leadership style, promotion, and work stress influence the performance of PT employees. Perkebunan Nusantara IV Reglonal II Kebun Adolina simultaneously and significantly. Leadership style does not affect the performance of PT employees. Perkebunan Nusantara IV Regional II Kebun Adolina significantly, but promotions affect the performance of PT employees. Perkebunan Nusantara IV Regional II Adolina Gardens significantly